EVALUASI IN VITRO-IN VIVO FILM TRANDERMAL DILTIAZEM HCL DENGAN PENINGKAT PENETRASI PEG 400 SEBAGAI ANTIHIPERTENSI - Yulias Ninik Windriyati; Risha Fillah Fithria; Fitria Dwi Kurniawati; Ulfa Risalatul Mukaromah (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2019)
ABSTRACTDiltiazem HCL is an antihypertensive that low oral bioavailability of 40%, so developed to transdermal preparations. A matrix type of transdermal patch of diltiazem HCl was prepared using polyvinyl alcohol and ethyl cellulose with PEG 400 as penetration enhancer. In vitro-in vivo evaluation were conducted to asses drug permeation through the skin and determine the effectiveness of transdermal film as an antihypertensive drug. Transdermal patches of diltiazem HCl were evaluated for physicochemical characteristics weight variation, thickness, folding endurance, moisture uptake, and drug content. In vitro permeation study was conducted using commercial semi permeable membrane in Franz diffusion cell. In vivo activity study was evaluated on male rat Wistar that induced NaCl with CODA non-invasive blood pressure method. Transdermal patches of diltiazem HCl were found no significant differences in terms of physicochemical characteristics. The in vitro skin permeation profiles showed increased flux values with the increase of PEG 400 as a penetration enhancer. The in vivo evaluation showed a reduction in systolic and diastolic blood pressure within one hour after the drug administration. Diltiazem HCl was able penetration into skin, absorbed in blood circulation and effective as antihypertensive via transdermal route.Keywords : antihypertension, diltiazem HCl, PEG 400, transdermal patch